Nitrogen-containing heterocycle derivatives, pharmaceutical compositions, and methods of use thereof as antiviral agents (2007)
The present application provides nitrogen-containing heterocycle derivatives that are antiviral compounds that may be useful in the treatment of a viral infection. Compounds of Formula (I) and pharmaceutical compositions comprising a compound of Formula (I) may be administered to a subject for antiviral therapy or prophylaxis.